Human iPSCs and Genome Editing Technologies for Precision Cardiovascular Tissue Engineering - Gähwiler, Eric K. N.; Motta, Sarah E.; Martin, Marcy; Nugraha, Bramasta; Hoerstrup, Simon P.; Emmert, Maximilian Y. (Frontiers in Cell and Developmental Biology, 2021)
Induced pluripotent stem cells (iPSCs) originate from the reprogramming of adult somatic cells types using four Yamanaka transcription factors. Since their discovery, the field of stem cell achieved significant milestones and opened several gateways in the area of disease modeling, drug discovery, and regenerative medicine. In parallel, the emergence of clustered regularly interspaced short palindromic repeats (CRISPR)-associated protein 9 (CRISPR-Cas9) revolutionized the field of genome engineering, allowing the generation of genetically-modified cell lines and achieve a precise genome recombination or random insertions/deletions, usefully translated for wider applications. Cardiovascular diseases represent a constantly increasing societal concern, with limited understanding of the underlying cellular and molecular mechanisms. The ability of iPSCs to differentiate into multiple cell types combined to CRISPR-Cas9 technology could enable the systematic investigation of pathophysiological mechanisms or drug screening for potential therapeutics. Furthermore, these technologies can provide a cellular platform for cardiovascular tissue engineering approaches by modulating the expression or inhibition of targeted protein, thereby creating the possibility to engineer new cell lines and/or fine-tune biomimetic scaffolds. This review will focus on the application of iPSCs, CRIPSR-Cas9, and a combination thereof to the field of cardiovascular tissue engineering. In particular, the clinical translatability of such technologies will be discussed ranging from disease modeling, to drug screening and tissue engineering applications.